Are Overconfident CEOs Better Innovators? - HIRSHLEIFER, DAVID; LOW, ANGIE; TEOH, SIEW HONG (Journal of Finance, 2012)
ABSTRACT Previous empirical work on adverse consequences of CEO overconfidence raises the question of why firms hire overconfident managers. Theoretical research suggests a reason: overconfidence can benefit shareholders by increasing investment in risky projects. Using options‐ and press‐based proxies for CEO overconfidence, we find that over the 1993–2003 period, firms with overconfident CEOs have greater return volatility, invest more in innovation, obtain more patents and patent citations, and achieve greater innovative success for given research and development expenditures. However, overconfident managers achieve greater innovation only in innovative industries. Our findings suggest that overconfidence helps CEOs exploit innovative growth opportunities.